Impacts of key environmental variables on suitable cultivation and flavonoid accumulation in Pueraria montana var. lobata under climate change in China - Yankun Li; Yuanxin Li; Zhuoyan Chen; Xinyi Yang; Qiuyue Zuo; Mingli Hu; Shimeng Li; Xinyi Teng; Chunsong Cheng; Qiqing Cheng (PLoS ONE, 2026)
Pueraria montana var. lobata ( P. lobata ) is both a medicinal herb with significant pharmacological values and a food ingredient that can replace grains, but it still faces challenges in quality consistency and suitable cultivation. This study aims to systematically analyze its potential suitable habitats across China and evaluate the effect of environment on its growth and quality. By integrating distribution data from 926 sample points and 33 environmental variables, MaxEnt model and ArcGIS software were employed to predict the potential suitable habitats of P. lobata , and investigate distribution change at the provincial level. Chemical and correlation analysis were used to determine the total flavonoid content and explore the relationship with environmental variables. Key influencing variables were Bio12 (annual precipitation, 35.4%), Bio14 (driest month precipitation, 24%), and Bio06 (coldest month minimum temperature, 18.2%). P. lobata from Hubei and Jiangxi provinces exhibited higher flavonoid content than that in other high-suitable provinces, which showed a strong positive correlation with latitude and a significant negative correlation with January mean temperature. Under future climate scenarios, the suitable habitats of P. lobata showed northward expansion due to global warming. These findings offer a theoretical foundation for sustainable development and high-quality demand under changing climatic conditions.